A Review of User Authentication Model for Online Banking System based on Mobile IMEI Number. Issue 1 (February 2020) - Hammood, Waleed A.; Abdullah, Ruzaini; Hammood, Omar A.; Mohamad Asmara, Salwana; Al-Sharafi, Mohammed A.; Muttaleb Hasan, Ali
Abstract: The traditional banking system, such as transactions over the counter using bank book is enhanced by adding the elements of electronic banking, where nowadays all transaction can be done over the network, because of globalization and the advancement of information and communication technology. However, significant threats to this technology also come in parallel, such as from banking frauds. This is why building trust among banking users by providing security mechanisms is very important. In the electronic banking, security mechanisms mainly focus on proving a secure environment for the online transaction, especially user authentication. Many researchers have been proposed various models for the online user access authentication for the banking industry. Most of the researches are based on traditional the form of username and password, but with the varying mechanism of password forms. For example, password in arbitrary value, password in arbitrary value through secured channel, as well as biometric like fingerprint recognition, voice recognition, or retina recognition. In this paper we reviewed the current existing user access for online banking based on mobile phone, the functions of the SIM card, the characteristics mobile of the SIM card are described. Cloning, a threat to the SIM card is also described. Findings show that all the security model for online user access contains password in the form of value, biometric, or PIN. Thus, none of the existing user access proposed the idea of the user access based on International Mobile Equipment Identity (IMEI) number to strength the security of the user access. The IMEI is a 15- or 17-digit code that uniquely identifies mobile phone sets.